Systems Pharmacology–Based Dissection of Anti-Cancer Mechanism of Traditional Chinese Herb Saussurea involucrata - Zhang, Qian; He, Lanyu; Jiang, Qingqing; Zhu, Hongqing; Kong, Dehua; Zhang, Hua; Cheng, Zhiqiang; Deng, Hongtao; Zheng, Yaxin; Ying, Xue (Frontiers in Pharmacology, 2021)
Cancer causes the highest mortality for human health worldwide and the development of effective drugs remains a key issue. Traditional Chinese medicine Saussurea involucrata(SI) exhibits a series of effects, such as anti-cancer, but the action mechanisms are still unclear. Here, systems pharmacology was applied to revealed its anti-cancer mechanism. First, we screened the active compounds of SI. Then, the compound-target network, target-disease network and target-pathway network were constructed. DAVID was applied for GOBP analysis and KEGG pathway enrichment analysis on cancer-related targets. Seven potential compounds and 187 targets were identified. The target-disease classification network showed that compounds mainly regulated proteins related to cancer, nervous system disease and cardiovascular system disease. Also, SI antitumor effect mainly associated to the regulation of NO production, angiogenesis, MAPK and PKB from GOBP enrichment. Additionally, KEGG pathway enrichment indicated that targets involved with anti-inflammatory, inhibiting angiogenesis, anti-proliferation or inducing apoptosis. Experimental validation showed that four active compounds could inhibit cell proliferation and promoted apoptosis in A549(except for kaempferol), PC-3 and C6 cells. This study not only provides experimental evidence for further research on SI in cancer treatment, but promotes the development of potential drugs of SI in modern medicine.